Smart Governance dan Tantangan Pelayanan Publik Inklusif bagi Kelompok Rentan - Yuli Santri Isma; Pangeran Putra Perkasa Alam Nasution; Fitria Akmal; Jamiati KN; Sarrah Kurnia Fadhilah (Jurnal Kajian dan Penelitian Umum, 2026)
Smart governance has become a primary instrument for governments to enhance efficiency and effectiveness in public service delivery. However, the rapid migration of public services to digital platforms carries a risk of excluding vulnerable groups, including the elderly, persons with disabilities, marginalized women, the poor, and communities living in remote areas. This article aims to analyze the development of smart governance in public services, identify challenges faced by vulnerable groups in accessing digital services, and formulate strategies to strengthen inclusive smart governance. Employing a systematic literature review approach, this study synthesizes findings from academic articles, policy documents, and international organization reports published between 2018 and 2025. The analysis reveals a fundamental paradox: while digital transformation of governance has improved service efficiency for those with adequate digital access and literacy, it simultaneously creates new barriers for vulnerable groups. Three main challenges are identified: limited digital infrastructure access, low digital literacy, and service design that has not fully adopted universal accessibility principles. Digital exclusion not only harms social justice but also threatens the legitimacy of democratic governance and accelerates existing social inequalities. This article proposes a multidimensional strategy comprising equitable infrastructure expansion, universal design implementation, community-based digital literacy programs, participatory co-production mechanisms, responsible data governance, and ongoing inclusive impact evaluations. This article contributes to the development of digital governance that is not solely oriented toward technological efficiency but also toward social justice and inclusive public services.